Resepsi Khalayak terhadap Konten 'Fact Psikologi' di TikTok @Afityaputri Terkait Cyberchondria - Ardi, Dwi Nurul Maulidya; Esfandari, Diah Agung (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The digitalization of information has reshaped how people consume and interpret health information. In Indonesia, the rapid increase of internet users has encouraged the public to seek health knowledge online, often leading to self-diagnose and excessive anxiety known as Cyberchondria. Although existing studies discuss this phenomenon, most emphasize psychological correlations rather than audience interpretation, leaving a theoretical gap regarding how mental health content on social media is received. This study addresses that gap by analyzing audience reception of the “Fact Psikologi” content on the TikTok account @afityaputri, which may trigger Cyberchondria. Employing a qualitative method with Stuart Hall’s reception analysis, the research identifies audience decoding positions (dominant hegemonic, negotiated, and oppositional) and Cyberchondria dimensions (compulsion, distress, excessiveness, seeking reassurance, and mistrust of medical professionals). The findings indicate that most participants occupy a negotiated position, considering the content educational and relevant, yet anxiety-inducing and prone to promoting excessive information seeking. Theoretically, this research expands Stuart Hall’s reception theory within digital media and mental health contexts. In conclusion, the TikTok content is ambivalent, informative yet capable of provoking Cyberchondria, emphasizing the importance of developing critical digital literacy among audiences.